A new model for fracability evaluation with consideration of natural cracks. (2nd May 2018) - Wang, Xiaoqiong; Ge, Hongkui; Han, Peng
Abstract: Fracability refers to the degree of difficulty to which shale gas plays can form complex fracture networks under hydraulic fracturing. Effective assessment of the fracability of a fracture network is an important part of shale gas reservoir evaluation. At present, the brittleness coefficient is used to characterize the fracability of shale reservoirs. The commonly used evaluation methods are elastic modulus characterization and the mineralogy composition ratio method. However, the influence of natural cracks on fracability is not considered. In this study, natural cracks are considered important influencing factors. A new model for evaluating the joint effects of matrix brittleness and natural cracks is proposed. The proposed method and model for evaluating the fracability are applied and verified by the Chongqing shale gas reservoir cores and measured well logging data. The results show that the fracability of Niutitang shale is better than that of Lujiaping shale, and the fracability of Lujiaping shale is better than Longmaxi shale. The comparison of the results calculated from the model with the imaging logging results shows that the new model is more reasonable than the existing models of brittleness coefficient.